MODEL OF ENHANCEMENT PERFORMANCE FOR HUMAN RESOURCE THROUGH SMART WORK PATTERN AND PROFESSIONAL COMPETENCE AS WELL AS WORK EXPERIENCE IN THE CONTEXT OF INFORMATION AND TECHNOLOGY USAGE EXPERIENCE - Hidan Noormantama; Widodo Widodo (UNISSULA, 2017)
The purpose of this study is to describe and analyze the effects of Smart Work Pattern, Professional Competence Level and Work Experience on human resource performance in the context of Information Technology Usage Experience. The number of respondents in this study was 244 ASN in 4 Government Agencies namely Inspectorate of Central Java Province, Semarang City, Kendal District and Demak District. Hypothesis testing used was Structural Equation Modeling (SEM) with SmartPLS ver.3 software. The results showed that with moderation of IT usage experience resulted in total effects of Professional Competence and Work Experience to the improvement of human resource performance through Smart Working Pattern was smaller thanthe total effects before moderation, it means that IT usage experience variable does not strengthen the effects of Professional Competence – Human Resource Performance; Work Experience - Human Resources and Smart Work Performance – Human Resource Performance.Keywords: Human Resource Performance, Work Experience, Professional Competence, Smart Working Pattern, IT Usage Experience